Kemukjizatan Al-Qur’an dalam Pembuktian Sains Modern - wirda wati; Alfiah Alfiah; Sylvia Sofian (Journal on Education, 2023)
The Qur'an is a miracle passed down by the Prophet Muhammad SAW. Miracles are extraordinary events that occur through a person who claims to be the Prophet, as his prophetic evidence, who is given to the doubtful, to do or bring about the same, but they are unable to serve the challenge. Only Allah is able to give miracles to the Prophet, one of which is the Prophet Muhammad in the form of the Qur'an. The Qur'an is a guide for Muslims in which there are rules of command and prohibition. There are so many in the Qur'an the evidences described about the miracles of the Prophets are even related to Science. Science is a science in which there is an element of fact. This was already proved before the creation of heaven and earth. Then the evidence of the miracles of the Qur'an can be seen in the surrounding natural phenomena related to science.